Analysis of Effect Agricultural and Domestic Activities on Water Quality and Macrozoobenthos in River of Batu City, A Case Study in Sisir and Pandanrejo Village - Cahyani Cahyani; Bagyo Yanuwiadi; Arief Rachmansyah (Indonesian Journal of Environment and Sustainable Development, 2020)
Batu city is located in East Java, the city has an important role in maintaining the quality of the river water. The city has developed into intensive agricultural and residential areas – services, which may reduce the water quality. This research was conducted in two areas with different dominating activities, in Sisir village (residential area) and in Pandanrejo village (agricultural area). The aims of this study are to analysis differences in water quality between the one in agricultural area and the one in residential area, and to analysis the water quality based on the diversity of macrozoobenthos. The water and macrozoobenthos samples were taken in upstream, midstream and downstream of the river. Water sample and macrozoobenthos sample were taken in different times. Calculate diversity of macrozoobenthos use Shannon-Wiener’s formula. The results showed that agricultural and domestic activities affect the concentration of chemical compounds in river. It concluded that chemical quality of the water in the agricultural activities and in the domestic activities showed the highest concentration of nitrate, and based on diversity of macrozoobenthos the quality of water in Sisir and Pandanrejo village are classified having moderate ecological pressure to high ecological pressure.